The lexicon of religious tourism: a contrastive Spanish-French approach - López Santiago, Mercedes (Círculo de Lingüística Aplicada a la Comunicación, 2019)
Religious tourism is a tourism activity that concerns more than 300 million tourists worldwide, according to UNWTO. In this work, we will describe the form and content of the section offered in the portal www.spain.info/es on religious tourism in Spain. The study of the lexicon used in this section will allow us to observe how this tourism is promoted and what are the arguments used, in addition to religious motivation, to promote this tourism. Finally, we will analyse the translated version in French of the section dedicated to the religious tourism in the portal www.spain.info/fr, focusing on the culture-bound terms. The purpose of this work is to contribute to the study of the lexicon of religious tourism from a contrastive Spanish-French perspective.
Keywords: Lexicology; culture-bound terms; Spanish-French contrastive linguistics; religious tourism